Evaluasi Kinerja Protokol Perutean AODV dan SDGR+R pada VANET dengan Studi Kasus Pelabuhan Lembar - Valian Yoga Pudya Ardhana; Esther Sanda Manapa; Tommy Wijaya Sagala; Yonathan Anggian Sihaan; Eliyah Acantha M Sampetoding (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
The Vehicular ad-hoc Network (VANET) is a subclass of Mobile ad-hoc networks (MANETs).VANET is a wireless network created from the concept of building a vehicle network (node) toexchange data information (data communication). There is a new concept technique forVANET communication used, namely the use of the concept of Software Defined Network(SDN) on VANET. For data communication between vehicles, a routing protocol required. Themost common routing protocol used on VANET since 2003 is AODV. In 2014 several studieswere using the SDN paradigm tried on VANET technology to improve the performance ofQuality of Service (QoS), one of which is a Geographic-based SDN, called SDGR in 2016.Multicast is a method of routing data on a network that allows one node or a group of nodes tocommunicate efficiently with the receiving node. The multicast concept supports one-to-manyrouting in nodes that send packet data to a group of nodes. The development of the SDGRrouting protocol using the idea of multicast technique to SDGR based on the Direction calledSDGR + R carried out in 2019. This study uses a case study of vehicle transportationsimulations in the Lamber Port area of Lombok. The simulation results knew that SDGR + Ris better than AODV in terms of service quality (QoS) at a latency of 15.58% and packet deliveryratio (PDR) of 47.78%.